2D ANIMATION IN AYOSCAN'S BRAND IDENTITY MOBILE APPLICATION - Arsita Pinandita; Novan Edo Pratama; Luqman Wahyudi (PT. Berkah Digital Teknologi, 2022)
A brand identity is a source of reputation and credibility for a company that can attract consumers uniquely. Therefore, a strong corporate branding strategy will become a competitive advantage and an essential intangible asset in the company's business processes. One way is with 2D animation, where animation, a brand can convey a message with its product, as well as the Ayoscan mobile application, which tries to display 2D animation into the mobile application in order to get Brand Positioning among users of the mobile application for public transportation payments.